Motivation From a Self-Regulated Learning Perspective: Application to School Psychology. (March 2022) - Bakhtiar, Aishah; Hadwin, Allyson F.
Self-regulation of learning involves developing metacognitive awareness (planning, monitoring, and evaluating) of (a) cognition—motivational beliefs, (b) behaviors—persistence, effort, engagement, and (c) affect—enjoyment, interest, and other emotions. Metacognitive awareness creates opportunities to exert metacognitive control as needed, which may involve sustaining or manipulating motivational cognition, behavior, and affect. By adopting a self-regulation perspective, this paper discusses the ways motivation develops within and across academic tasks and situations, as well as the ways learners can be supported to take control of their motivation in those contexts. Applying self-regulation principles in the practice of School Psychology means to consider the role of situation, context, and learners' socio-historical experiences while empowering learners to focus attention on things they can control.